Environmental Management and Justice System in Bangladesh: Issues and Legal Framework - Abdullah-Al-Monzur Hussain; Md Hasnath Kabir Fahim; Ramisa Jahan (APPTHI, 2025)
This paper presents environmental justice in Bangladesh, which is connected with the human development, implementation, and enforcement of environmental laws, regulations, and policies. Environmental justice is essential for human rights, which affects human lives as well as the sustainable development of the country. Environmental justice ensures all people’s enjoyment of human rights, economic development, and health protection; above all, a healthy environment for life. Various environmental issues like global warming, overpopulation, waste disposal, ocean acidification, loss of biodiversity, and deforestation are harmful to human lives. The environmental problems in Bangladesh are climate change, cyclones, floods, drought, earthquakes, riverbank erosion, air pollution, water pollution, soil pollution, noise pollution, etc.